A hydroxamic acid–methacrylated collagen conjugate for the modulation of inflammation-related MMP upregulation. Issue 22 (22nd May 2018) - Liang, He; Russell, Stephen J.; Wood, David J.; Tronci, Giuseppe
Abstract : The selective covalent coupling of hydroxamic acid functions on to methacrylated type I collagen led to UV-cured networks with inherent MMP-modulating capability and enhanced proteolytic stability. Abstract : Medical devices with matrix metalloproteinase (MMP)-modulating functionality are highly desirable to restore tissue homeostasis in critical inflammation states, such as chronic wounds, rotator cuff tears and cancer. The introduction of MMP-modulating functionality in such devices is typically achieved via loading of either rapidly diffusing chelating factors, e.g. EDTA, or MMP-cleavable substrates, raising issues in terms of non-controllable pharmacokinetics and enzymatic degradability, respectively. Aiming to accomplish inherent, long-term, device-induced MMP regulation, this study investigated the synthesis of a hydroxamic acid (HA)–methacrylated collagen conjugate as the building block of a soluble factor-free MMP-modulating hydrogel network with controlled enzymatic degradability. This was realised via a two-step synthetic route: (i) type I collagen was functionalised with photonetwork-inducing methacrylic anhydride (MA) adducts in the presence of triethylamine (TEA); (ii) this methacrylated product was activated with a water-soluble carbodiimide prior to reaction with hydroxylamine, resulting in MMP-chelating HA functions. Nearly-quantitative methacrylation of collagen amines was observed via 2, 4, 6-trinitrobenzenesulfonic acid (TNBS) assay; this was key to avoiding intramolecular crosslinking side reactions during the carbodiimide-mediated activation of collagen carboxyl groups. The molar content of HA adducts was indirectly quantified via the conversion of remaining carboxyl functions into ethylenediamine (EDA), so that 12–16 mol% HA was revealed in the conjugate by both TNBS and Ninhydrin assays. Resulting UV-cured, HA-bearing collagen hydrogels proved to induce up to ∼13 and ∼32 RFU% activity reduction of MMP-9 and MMP-3, respectively, following 4-day incubation in vitro, whilst displaying an averaged mass loss in the range of 8–21 wt%. Dichroic and electrophoretic patterns of native type I collagen could still be observed following the introduction of HA adducts, suggesting preserved triple helix architecture and chemical sequence in respective HA–methacrylated collagen conjugate. No hydrogel-induced toxic response was observed following the 4-day culture of G292 cells, whilst a lower compression modulus and gel content were measured in HA-bearing compared to methacrylated hydrogels, likely related to HA radical scavenging activity. The novel synthetic strategies described in this work provide a new insight into the systematic chemical manipulation of collagen materials aiming at the design of biomimetic, inflammation-responsive medical devices.